2021
DOI: 10.2196/28311
|View full text |Cite
|
Sign up to set email alerts
|

Privacy and Confidentiality Concerns Related to the Use of mHealth Apps for HIV Prevention Efforts Among Malaysian Men Who Have Sex With Men: Cross-sectional Survey Study

Abstract: Background The use of mobile health (mHealth), including smartphone apps, can improve the HIV prevention cascade for key populations such as men who have sex with men (MSM). In Malaysia, where stigma and discrimination toward MSM are high, the mHealth platform has the potential to open new frontiers for HIV prevention efforts. However, little guidance is available to inform researchers about privacy and confidentiality concerns unique to the development and implementation of app-based HIV preventio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
3
4
0
Order By: Relevance
“…Among our sample of MSM, concerns about privacy and confidentiality were substantial, bringing forth the issue of third-party data interception, which can occur by accidental disclosure or deliberately through governmental access and subpoena. This finding accentuates previously reported concerns among MSM subgroups regarding the unintentional disclosure of sensitive information to nearby users [ 31 ] and further highlights the need for app developers to incorporate app features that address the privacy and confidentiality concerns. Other MSM subgroups have also emphasized their fear of being inadvertently “outed” within their respective communities if they use such platforms in public [ 50 ].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Among our sample of MSM, concerns about privacy and confidentiality were substantial, bringing forth the issue of third-party data interception, which can occur by accidental disclosure or deliberately through governmental access and subpoena. This finding accentuates previously reported concerns among MSM subgroups regarding the unintentional disclosure of sensitive information to nearby users [ 31 ] and further highlights the need for app developers to incorporate app features that address the privacy and confidentiality concerns. Other MSM subgroups have also emphasized their fear of being inadvertently “outed” within their respective communities if they use such platforms in public [ 50 ].…”
Section: Discussionsupporting
confidence: 69%
“…mHealth platforms are well placed to fill this gap, as they provide a web-based platform to deliver HIV services, especially in countries such as Malaysia where MSM are well connected to the internet and use smartphones to seek sexual health information on the web [ 29 ]. The findings of this study are critical to assist the development of ethically sound app-based HIV prevention programs, which require the engagement of MSM early on [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, concerns about data privacy, e.g., when the app emits warning messages, constitute a characteristic both groups have in common. This is similar to other studies which have already shown that people living with HIV have a high level of awareness regarding the privacy and security of their health data [51,52]. The design and implementation of the app must ensure that patients using the app in their daily lives cannot be identified by other people as HIV-infected individuals or PrEP users.…”
Section: Organizational Conditionssupporting
confidence: 79%